PENGARUH KEADILAN, SELF ASSESSMENT SYSTEM, DISKRIMINASI, DAN KEMUNGKINAN TERDETEKSINYA KECURANGAN TERHADAP PERSEPSI WAJIB PAJAK DALAM TINDAKAN PENGGELAPAN PAJAK (Studi Empiris Pada Wajib Pajak Badan yang Terdaftar Di KPP Pratama Tampan Pekanbaru) - Damayanti, Dini; Nasir, Azwir; Paulus, Sem (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
the research aims to examine the influence of fairness, self assessment system, discriminant and the probability of cheat detact to taxpayer perceptions about tax evasion. Object of this research taxpayer were registered in KPP Pratama Pekanbaru. There are one hundred questionnaires were sent, but only fourty four questionnaires were returned. That data are analyzed by multiple regression method and SPSS program version 19. The variables were examined are influence of fairness, self assessment system, discriminant and the probability of cheat detact to taxpayer perceptions about tax evasion. The results of this research showed that fairness has an effect on taxpayer perceptions about ta evasion with 0,000 significance, the self assessment system has an effect on taxpayer perceptions about tax evasion with 0,000 significance, discriminant has no effect on taxpayer perceptions about tax evasion with 0,427 significance and the probability of cheat detact has an effect on taxpayer perceptions about tax evasion with 0,006 significance. The results of this research also showed that coefficient determinant is 89,1%. Each independent variables, gives the strong influence to dependent variable, it means independents variables could explain dependent variable well. While the remaining influenced by other variables not included in the regression models were not included in this study. All variables also have strong relation with variable dependents in this research.Keywords: fairness, self assessment system, discriminant, cheat detact and tax evasion